Peran OJK Dalam Mempertahankan Good Corporate Governance Dalam Industri Fintech Untuk Keberlanjutan Kepuasan Konsumen - Ahmad Farhan Hadad (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The widespread use of internet technology in Indonesia has driven rapid growth in the fintech industry. In the fintech industry, significant growth in demand needs to be balanced with adequate supply. In this context, as a service provider platform, implementing Good Corporate Governance (GCG) is crucial to protect consumer rights and ensure smooth supply and demand dynamics, especially in the case of peer-to-peer (P2P) lending, where there are both legal and illegal P2P lending syndicates. Therefore, legal regulations governing the P2P lending process in accordance with GCG principles are necessary. The Financial Services Authority (OJK), as the financial supervisory authority, acts in accordance with Article 4 of Law No. 21 of 2011 concerning the Financial Services Authority. Furthermore, the OJK has provided practical regulations for the registration and licensing of P2P lending in Indonesia through OJK Regulation No. 77/0.1/2016. Additionally, the OJK plans to update these regulations regarding GCG in the fintech P2P lending industry. Applying Good Corporate Governance (GCG) to update these regulations regarding GCG in the fintech P2P lending industry is crucial for service provider platforms because these updates are aimed at protecting consumer rights and ensuring smooth supply and demand dynamics, especially in the case of P2P lending where there are legal and illegal P2P lending syndicates. Therefore, legal regulations governing the P2P lending process in accordance with GCG principles are necessary.Keywords: Good Corporate Governance; Otoritas Jasa Keuangan; Peer-to-Peer Landing AbstrakPenggunaan teknologi internet yang luas di Indonesia telah mendorong pertumbuhan pesat dalam industri fintech. Dalam industri fintech, pertumbuhan signifikan dalam permintaan perlu seimbang dengan pasokan yang memadai. Dalam konteks ini, sebagai platform penyedia layanan, menerapkan Tata Kelola Perusahaan yang Baik (GCG) sangat fundamental untuk melindungi hak-hak konsumen dan memastikan dinamika pasokan dan permintaan yang lancar, terutama dalam kasus P2P lending, di mana terdapat sindikat P2P lending legal dan ilegal. Oleh karena itu, diperlukan regulasi hukum yang mengatur proses P2P lending sesuai dengan prinsip-prinsip GCG. Otoritas Jasa Keuangan (OJK), sebagai otoritas pengawas keuangan, bertindak sesuai dengan Pasal 4 Undang-Undang No. 21 tahun 2011 tentang Otoritas Jasa Keuangan. Selain itu, OJK telah menyediakan regulasi praktis untuk registrasi dan perizinan P2P lending di Indonesia melalui Peraturan OJK No. 77/0.1/2016. Selanjutnya, OJK berencana untuk memperbarui regulasi-regulasi ini mengenai GCG dalam industri fintech P2P lending. Menerapkan Tata Kelola Perusahaan yang Baik (GCG) untuk memperbarui regulasi-regulasi ini mengenai GCG dalam industri fintech P2P lending sangat fundamental bagi platform penyedia layanan, sebab pemberharuan tersebut ditujukan untuk melindungi hak-hak konsumen dan memastikan dinamika pasokan dan permintaan yang lancar, terutama dalam kasus P2P lending, di mana terdapat sindikat P2P lending legal dan ilegal. Oleh karena itu, diperlukan regulasi hukum yang mengatur proses P2P lending sesuai dengan prinsip-prinsip GCG.Kata Kunci: Good Corporate Governance; Otoritas Jasa Keuangan; Peer-to-Peer Landing